Financial Added Value To Increase Profitability: Processed Fish Waste Into Fish Feed Pellet Product In MSMEs “Kemuning Mandiri” - Purwanto, Setiyo; Wuryandari, Nur Endah Retno (Institute of Education and Social Research, 2025)
Community service activities carried out by Dian Nusantara University (UNDIRA) lecturers to help develop business opportunities in the catfish processing industry are carried out by some home industry communities who call themselves the